Spectral Analysis of Data Generated by Simulation Experiments with Econometric Models - Naylor, Thomas H.; Wertz, Kenneth; Wonnacott, Thomas H. (Econometrica, 1969)
This paper is concerned with the use of spectral analysis to analyze data generated by computer simulation experiments with models of economic systems. An example model serves to illustrate two different applications of spectral analysis. First, spectral analysis is used to construct confidence bands and to test hypotheses for the purpose of comparing the results of the use of two or more alternative economic policies. Second, spectral analysis is employed as a technique for validating an econometric model.